The Relationship between Emotional Intelligence and Table Tennis Motivation at the UPI Table Tennis Student Activity Unit, Sumedang Campus - Erwin Dwi Meilinda; Indra Safari; Dewi Susilawati (Universitas Pendidikan Indonesia, 2021)
This research is motivated by the experience of field findings. In the findings of researchers at the UPI Sumedang table tennis UKM, there were often UKM members who were lazing about practicing table tennis. The purpose of this study was to determine the relationship between emotional intelligence and table tennis motivation in UPI Sumedang table tennis UKM with 31 members of UKM consisting of 16 boys and 15 girls. This research method uses correlation with a simple correlation design. Meanwhile, the data collection used in this research is the emotional intelligence test using the emotional intelligence questionnaire test, and for the table tennis motivation test using the table tennis motivation questionnaire test. Sig value. (2-tailed) the relationship between emotional intelligence and table tennis motivation is 0.000 0.05, there is a relationship between emotional intelligence and table tennis motivation. The pearson correlation value is 0.677 which is included in the degree of strong correlation. It can be concluded that there is a significant relationship between emotional intelligence and table tennis motivation at the UPI Sumedang table tennis UKM.